DIFFERENCES IN SOIL INFILTRATION CAPACITY IN TWO VEGETATION COVER TYPES IN THE PERUVIAN AMAZON - GARATE-QUISPE, Jorge Santiago (2022)
The rapid urban and agricultural expansion cause severe impacts on soil water infiltration capacity, but these effects have not yet been sufficiently investigated, especially in the Peruvian Amazon. The study aimed to analyze the variations in speed and soil infiltration in two vegetation cover types (primary intervened forest and pasture) in the Peruvian Amazon. The infiltration rate of the soil was measured using the single ring infiltrometer; three samples were collected in the pasture and six in the primary forest. With the values obtained, the infiltration curves were constructed. To evaluate differences in infiltration capacity between cover vegetation types, we used the t‑Student test. Our results show that the infiltration capacity in the primary forest was greater than in the pasture (p ≤ 0,01, t‑Student test). Regarding the physicochemical characteristics of the soil, we found no significant differences between the two types of cover studied. The abundance, species richness, and vegetation diversity were positively associated with the infiltration capacity (p ≤ 0,05). We conclude that the soil water infiltration capacity in primary intervened forest is higher than in pastures. This would have significant impacts on the hydrological behavior of the tropical ecosystems due to the transformation of forests into pastures generated by anthropogenic activities. the two types of cover studied. The abundance, species richness, and vegetation diversity were positively associated with infiltration (P ≤ 0.05). We conclude that the soil water infiltration rate in primary forests is higher than in pastures. This would have significant impacts on the hydrological behavior of tropical ecosystems due to the transformation of forests into pastures generated by anthropogenic activities.